IgG Expression upon Oral Sensitization in Association with Maternal Exposure to Ovalbumin. - Rucheng Chen; Xiaoqiao Tang; Bolin Fan; Jiafa Liu; Xudong Jia; Xiaoguang Yang (PLoS ONE, 2016)
The role of maternal allergen exposure in the allergenicity of the offspring remains controversial. Some studies have shown that maternal exposure is a risk factor for allergy in the offspring, whereas other studies have shown that maternal exposure induces immune tolerance and protects offspring from allergy disease. Therefore, we utilized maternal rat allergen exposure model to evaluate the offspring immune reactions to ovalbumin protein and to determine whether the Brown Norway (BN) rat model is a suitable animal model for studying the allergenicity of food proteins. For three generations, rats received an allergens or non-allergens by gavage during the pregnancy and lactation periods. After weaning, the offspring rats were used for oral sensitization experiment. In the sensitization experiment, the control rat, which had maternal exposure to phosphate-buffered saline (PBS), exhibited full response of IgG to oral exposure to OVA. The IgG level was significantly lower in F1 rats that were sensitized by maternal exposure to ovalbumin(OVA). Moreover, the lowest IgG level was found for the F3b sensitized by maternal rats exposed to OVA allergen for three continuous generations. Compared with maternal OVA exposure prior to postnatal sensitization, the sensitization via maternal PBS led to a higher serum level of OVA-specific IgG. However, the OVA-specific IgG levels for the two generations of maternal PBS exposure prior to postnatal sensitization was not higher than that for the one generation of maternal rats exposed to PBS prior to postnatal sensitization. Our studies demonstrate that maternal OVA exposure during the pregnancy and lactation can affect the results of oral sensitization studies using ovalbumin protein. BN rats must be bred in non-allergen conditions for at least one generation to avoid problems in rat models for studying the allergenicity of food proteins.